ANALISIS KELAYAKAN FINANSIAL PEMANFAATAN LIMBAH DARI KOTORAN SAPI UNTUK MENGHASILKAN BIOGAS (Studi Kasus: Peternakan Sapi Pondok Pesantren Khairul Ummah, Air Molek, Indragiri Hulu) - Miranti Mandasari; Yusmini Yusmini; Ermi Tety (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to analyze feasibility proper by using dump of cow waste to produce biogas. This research was to take a place at livestock Pondok Pesantren Khairul Ummah, conduct from Maret-April 2014. The used of data is primary data and secondary data, that have a simillar in quality and quantity. The value of investment criteria was used in this research is : Net Present Value (NPV), Net Benefit Cost Ratio(Net B/C), Internal Rate ofReturn (IRR), Payback Period (PP), and Analysis of Sensitivity if cost for cow waste has changed 10%. The value of Social Opportunity of Capital (SOCC) as discount factor is 12%. The value of Net Present Value (NPV) during age of business activity of equal toRp. 306.352.725,46. The value of Net Benefit Cost Ratio(Net B/C) is 5,14, that was meaning output Rp.1,00 will give back Rp. 5,14. The value of IRR is 51,53%, it was meaning the ability toreturn the capital is more than discount factor, and Payback Period of equal to28,61 months or about 4 year and 7 months, and it’s meaning return of investation the biodygester operate obtained after 4 years and 7 months. Analysissensitivity of the changed of cost input around 10%, NPV of equal toRp.232.770.721,58. The result of this search shows the development biogasat livestock Pondok Pesantren Khairul Ummah is feasible to be implement and develope. Keyword : biogas, investment criteria, financial analysis